Fasting time and stomach content in pigs slaughtering (Research, Society and Development, 2022)
The objective of this work was to observe, through the monitoring of pre-slaughter management and slaughter of pigs, the effects of fasting time on the farm (six, eight, ten and twelve hours) and the resting period of pigs in the slaughterhouse, as well as stomach content, average carcass weight and hot carcass yield. The observation was carried out in a large slaughterhouse in the State of Rio Grande do Sul, registered with the Serviço de Inspeção Federal (SIF), starting at the swine farm located near the slaughterhouse, where, prior to the day of slaughter, 320 females were divided in 4 batches of 80 animals and each batch received the last meal, six, eight, ten and twelve hours before the scheduled time for loading, with the rest of the period fasting on the farm. All management steps prior to slaughter were monitored to measure the times performed, as well as the slaughter of these animals for the collection of weight, yield and stomach contents, the latter being done by turning the contents of 35 units of stomachs per batch. The results found for the rest period and water diet of each batch at the slaughterhouse ranged from 07h:40min to 08h:40min, the total fasting time ranged from 21h:50 min to 16h:40 min, the weight of the total wet solid content found in the stomachs ranged from 704.90 g to 1,273.30 g, minimum weight of females was 92.10 kg and maximum weight of 96.85 kg, and yield ranging from 72.52% to 74.64%. The results presented for the fasting times of the applied pigs meet the standard of stomach content tolerated by the industry, without interfering with the average carcass weight, condemnation by contamination in evisceration and hot carcass yield.